Examining the Nonstationary Spatial Association Between International Migration and Vulnerable Older People Living Alone in Mexico - Rojas Huerta, Abigail Vanessa; Lara Lara, Jaime (Migration Letters, 2023)
Research on the intersection of migration and ageing is becoming increasingly relevant as older populations grow in developing countries. Understanding the challenges older people face, often left behind due to their vulnerable position, is essential for policy-making. This research examines the geographical variation in the impact of international migration on the living alone status of older people in Mexico, particularly those most at risk. The following municipal-level information was obtained from the 2020 Census: international migration, living alone, receipt of remittances, and disability. Using geographically weighted regressions, we found geographical variations in the association between international migration and living alone or being more vulnerable. Controlling for socio-demographic factors, in the southern states international migration is associated with a reduction in the proportion of adults living alone and vulnerability due to disability or lack of support from other households. This relationship holds for both men and women. However, in some border regions the proportion of older adults living alone and experiencing greater vulnerability increases with migration, especially for women.